A prospective observational trial evaluating factors predictive of accurate endotracheal tube positioning in neonates and small infants. Issue 8 (17th July 2020) - Ebenebe, Chinedu Ulrich; Deindl, Philipp; Wolf, Monika; Jahn, Matthias; Singer, Dominique; Blohm, Martin Ernst
Abstract: Background: There is a high incidence of endotracheal tube malposition in neonates and small infants. Yet, verification of accurate endotracheal tube location via radiographic imaging involves radiation exposure. Aims: This study aimed to identify demographic and clinical parameters associated with accurate endotracheal tube positioning. Methods: We conducted a prospective single‐center study with term and preterm neonates and small infants between January 2018 and November 2019. We investigated correlations between ten variables and accurate endotracheal tube position. Results: One hundred and sixty eight nasal intubations in 139 patients (weight 390‐5000 g) were analyzed. An accurate tube position was confirmed by radiographic imaging in 71.4% of the intubations. The endotracheal tube was high in 8.3% and low in 20.2% of the cases. Male gender was the only variable that significantly correlated with an accurate endotracheal tube position (OR 2.5; 95% CI: 1.3, 5.0; P = .010). Conclusion: So far, no parameter has proven to be able to predict accurate endotracheal tube position in neonates reliably. These findings emphasize the indispensability of postintubation imaging in neonates and small infants.